Utilização de modelos pedagógicos como ferramentas de ensino sobre arboviroses na Amazônia - Belchior, Heliana Christy Matos (Brasil, 2022)
Arboviruses are infectious diseases caused by arboviruses, which are transmitted by arthropods belonging to the order Diptera, these being the main vectors. Reports of these infections grow each year in the country and the northern region is always among the first three regions with the highest incidence of these diseases. These infections can be considered a social and environmental problem, since their causes are related to the various anthropic processes that modify the landscape and alter the biology and ecology of their vectors. Therefore, it is the role of the educator, together with the school system, to seek alternative praxis, such as didactic sequences and teaching models that help in the construction of the student's understanding of the dynamics of interactions between science, technology, society and environment, enabling the expansion of possibilities of understanding and effective participation of the student in the world. Thus the present work aimed to use the approach Science, Technology, Society and Environment in conjunction with the Generator Theme organized in Environmental Education and Health Education to contribute to discussions about arboviruses in teaching of biology. The work was applied with the students of the Biological Sciences Degree of the sixth period at the Amazonas Federal Institute, Manaus Centro Campus. The project was developed based on the three pedagogical moments, where the stages resulted from the application: a questionnaire, a dialogued lecture, a practical class and finally the students needed to solve a problem issue pertinent to the theme. Thus, it was possible to apply all the steps proposed in this work using the pedagogical models and the students were able to understand the importance of knowing the arboviruses, their vectors, their transmission cycles and factors that may influence the spread of these diseases.